Risk for schizophrenia and schizophrenia-like psychosis among patients with epilepsy: population based cohort study - Qin, Ping (BMJ Publishing Group Ltd., 2005)
Objectives To investigate whether age at onset of epilepsy, type of epilepsy, family history of psychosis, or family history of epilepsy affect the risk of schizophrenia or schizophrenia-like psychosis among patients with epilepsy. Design Comparison of population based data. Setting Danish longitudinal registers. Subjects The cohort comprised 2.27 million people. Main outcome measures Epilepsy, psychosis, personal birth data. Results We found an increased risk of schizophrenia (relative risk 2.48, 95% confidence interval 2.20 to 2.80) and schizophrenia-like psychosis (2.93, 2.69 to 3.20) in people with a history of epilepsy. The effect of epilepsy was the same in men and in women and increased with age. Family history of psychosis and a family history of epilepsy were significant risk factors for schizophrenia and schizophrenia-like psychosis, and the effect of epilepsy, both in cases and families, was greater among people with no family history of psychosis. In addition, the increased risk for schizophrenia or schizophrenia-like psychosis did not differ by type of epilepsy but increased with increasing number of admissions to hospital and, particularly, was significantly greater for people first admitted for epilepsy at later ages. Conclusions There is a strong association between epilepsy and schizophrenia or schizophrenia-like psychosis. The two conditions may share common genetic or environmental causes.